PENGARUH POSISI PRONASI TERHADAP PENURUNAN KADAR BILIRUBIN PADA BAYI NEONATUS - Wardeni, Resa; Rosuliana, Novi Enis; Herliana, Lia; Riyana, Asep (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2025)
Background: Hyperbilirubinemia in neonates is a yellowing of the skin, conjunctiva, and sclera of the baby caused by an increase in bilirubin levels in the plasma during the early life of the baby, which appears after a few days following birth. Efforts to manage the increase in bilirubin levels in infants include performing phototherapy and positioning the baby in a prone position every 2 hours, which can help reduce bilirubin levels in the baby. Purpose: Understanding the application of phototherapy and the prone position on the reduction of bilirubin levels in neonates. Method: The method used is through research in the form of a case study conducted in the Level 1 NICU (Perinatology) / Salman Al-Farizi on newborns (Neonates) who meet the inclusion and exclusion criteria, totaling two individuals, with data collection techniques consisting of interviews and observations. The pronation positioning intervention was carried out once a day for three days with a duration of 30 minutes every two hours. Results: To determine the effect of the prone position on the decrease in bilirubin levels after the administration of the action with patient 1 bilirubin levels to 10 mg / dL and patient 2 bilirubin levels to 11 mg / dL. Conclution: The prone position has been proven effective in reducing bilirubin levels in neonates, hospitals are expected to be able to implement the prone position to help reduce high bilirubin levels. Suggestion: For parents at home who have babies experiencing an increase in bilirubin levels or changes in skin color to yellowish, they can expose the baby to sunlight under direct sunlight from 07:00 to 08:00 AM WIB using available tools and materials as long as the light is able to reach the entire area of the baby's body.